Extracorporeal life support in a porcine model of septic endotoxemia with acute pulmonary hypertension: an experimental study - Sandrio, Stany; Krebs, Jörg; Spanier, Tobias; Beck, Grietje; Thiel, Manfred; Graf, Peter Tobias (Journal of Clinical Medicine, 2025)
Background: This study evaluated the effects of veno-arterial (V-A) and veno-venoarterial (V-VA) ECMO in a porcine model of septic endotoxemia-induced acute pulmonary arterial hypertension (PAH). Our hypotheses were as follows: (1) V-VA ECMO lowers pulmonary vascular resistance (PVR) by delivering oxygenated blood to the pulmonary circulation, and (2) both V-A and V-VA ECMO improve perfusion to vital organs while simultaneously unloading the right ventricle (RV). Methods: Acute PAH was induced with Salmonella abortus equi lipopolysaccharide (LPS) in 34 pigs. Animals were randomized to either a control group without ECMO or to two groups receiving V-A or V-VA ECMO. Results: All animals developed PAH after one hour of LPS infusion: mean pulmonary artery pressure (PAP) increased significantly from 26 (24-30) mmHg to 40 (34-46) mmHg (p < 0.0001), and PVR increased from 314 (221-390) to 787 (549-1073) (p < 0.0001). Neither V-A nor V-VA ECMO significantly reduced PVR compared to controls. RV end-diastolic area increased in the control group [6.1 (4.3-8.6) cm vs. 8.5 (7.8-9.7) cm, p = 0.2], but not in the V-A [4.7 (3.3-7.6) cm] and V-VA [4.3 (2.5-8.3) cm] ECMO groups. Blood flow in the cranial mesenteric artery and celiac trunk did not differ significantly with or without ECMO. Conclusions: Elevating pulmonary artery oxygen tension through V-A or V-VA ECMO did not reduce PVR or PAP. However, both ECMO configurations effectively unloaded the RV and maintained perfusion to abdominal organs.